A contextual family tree visualization design. (October 2019) - Borges, José
With the increase in availability of online national archives and software to manage genealogical records, genealogy studies are growing in popularity. While conducting research, genealogists communicate their findings either in written narratives or in genealogical charts. In that context, visualization methods can be very effective for promoting the understanding of the intricacies of a family tree and the relations among its individuals. Most of the software designed for genealogy provides a collection of standard charts to plot family trees, despite having limited analysis capabilities in general. In addition, most of the research in family tree visualization designs have been focused on methods to represent very large trees in a restricted space. Herein, we propose the contextual family tree, a new visualization design for family trees that represents individuals and their spouses with enhanced details about their families' context. The design was developed through an iterative prototype-evaluation design cycle. For illustrating the potential of our new visualization design, we used contextual family trees created from publicly available genealogical data communication files, showing that the design can be useful to provide a better understanding of the data and also for validating the consistency of the genealogical data.